PERENCANAAN PEMBUATAN PETA TATA GUNA LAHAN KECAMATAN PLAJU - Alfain, M. Hifzni; Mulyati, Ely (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Integrated land-use planning is a crucial step in supporting the sustainable management of regional resources. This study aims to create a land-use map for the Plaju District, covering the villages of Bagus Kuning, Plaju Ulu, Talang Bubuk, and Plaju Darat. The topic was chosen due to the need for accurate spatial information to support development planning and decision-making in the area. The data used in this study were sourced from the Palembang City Government Geoportal, aerial imagery from Google Maps, and the 2023 statistical data for the Plaju District. The map was created using QGIS software to ensure effective and accurate geospatial data processing. The results of this study produced a land-use map reflecting the current land use in the study area, including residential areas, green spaces, and public facilities. This map is expected to serve as a basis for regional planning, disaster mitigation, and better spatial planning. In conclusion, this land-use map not only contributes to enhancing spatial understanding of the Plaju District but also serves as a vital tool for supporting data-driven spatial planning policies. The implementation of QGIS in this study highlights the potential of geospatial technology in supporting sustainable regional management.Keywords: Geospatial technology, Land use, Plaju District, QGIS, regional planning